2023
DOI: 10.1002/14651858.cd008106.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus non-surgical interventions for treating patellar dislocation

Abstract: Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 2, 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Recurrent patellar dislocation is a common and debilitating condition with multifactorial aetiologies associated with various pathoanatomical factors, which usually affects young active children and adolescents [6,20,26]. Of all the anatomical variants, increased femoral torsion is a potential risk factor for recurrent patellar dislocation, which may exert a persistent lateralizing force vector on the patella and lead to increased tension of the reconstructed medial patellofemoral ligament (MPFL), thus causing anterior knee pain, patellar maltracking, early cartilage degeneration, graft failure and patellar redislocation [8,10,19,21,24,28,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent patellar dislocation is a common and debilitating condition with multifactorial aetiologies associated with various pathoanatomical factors, which usually affects young active children and adolescents [6,20,26]. Of all the anatomical variants, increased femoral torsion is a potential risk factor for recurrent patellar dislocation, which may exert a persistent lateralizing force vector on the patella and lead to increased tension of the reconstructed medial patellofemoral ligament (MPFL), thus causing anterior knee pain, patellar maltracking, early cartilage degeneration, graft failure and patellar redislocation [8,10,19,21,24,28,30].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is mainly reserved for concurrent injuries and when non-surgical treatment is unsuccessful [ 5 , 6 ]. Currently, recovery after non-surgical treatment is often incomplete with recurrent patellar dislocation and instability, reduced knee function, and later surgery commonly reported [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…37 Previous research focused on how trochlear dysplasia, joint alignment, patellofemoral soft tissue forces, and patient age contribute to the origin of LPD. 9,19,[23][24][25]39 This research highlights adolescent age, patella alta, and trochlear dysplasia as strong risk factors for acute and recurrent patellar dislocation. 3,18 More recently, researchers 37 have created predictive algorithms to identify individuals most at risk for recurrent dislocations, as a guide for interventional decision-making.…”
mentioning
confidence: 97%
“…12,19 In most cases, the primary treatment for initial LPD is nonoperative management (eg, bracing and physical therapy). 22,39 Surgical intervention may be necessary after a primary LPD associated with an osteochondral loose body. 19 A recent review demonstrated a lack of convincing evidence to change current practice guidelines for patients with first-time patellar dislocation (eg, nonsurgical vs surgical management).…”
mentioning
confidence: 99%